Trifluoroacetic acid as excipient destabilizes melittin causing the selective aggregation of melittin within the centrin-melittin-trifluoroacetic acid complex - Pastrana Rios, Belinda (2015)
Trifluoroacetic acid (TFA) may be the cause of the bottleneck in high resolution structure determination for protein-peptide complexes. Fragment based drug design often involves the use of synthetic peptides which contain TFA (excipient). Our goal was to explore the effects of this excipient on a model complex: centrin-melittin-TFA. We performed Fourier transform infrared, two-dimensional infrared correlation spectroscopies and spectral simulations to analyze the amide I’/I’* band for the components and the ternary complex. Melittin (MLT) was observed to have increased helicity upon its interaction with centrin, followed by the thermally induced aggregation of MLT within the ternary complex in the TFA presence.